Gender and school-stage associations with health-related behaviours and health-related quality of life in Spanish children - Knox, Emily; Muros Molina, Jose Joaquin (Taylor & Francis, 2017)
During adolescence individuals experience a number of cognitive, physical, psychological and emotional changes which can impinge on their health and wellbeing. The aim of this study was to identify associations with five components of health-related quality of life (HRQoL) in children. Data were collected from 456 children attending one of five schools in Granada, Spain in a cross-sectional design. Females reported engaging in less physical activity than males. Females reported lower HRQoL in terms of lower physical wellbeing, family relationships and autonomy and perceived school environment in secondary school. Males only reported lower perceptions of their school environment in secondary school. Physical activity was strongly associated with HRQoL, whereas Mediterranean diet was not. Physical activity interventions should be prioritised when positive HRQoL of children is a main target. Special consideration should be given to support the positive development of females, especially during the early years of secondary school.